A linguística de corpos e o seriado Friends como base para o ensino de chunks em sala de aula de língua inglesa - Vicentini, Giseli Previdente Martins (2006)
The aim of this study was to suggest a complementation of an activity from the coursebook InsideOut Upper Intermediate (Kay e Jones, 2001), through Corpus Linguistic analysis. The main theoretical underpinning for the research is provided by Corpus Linguistics, which is an area that is concerned with the collection and analysis of corpora, which are collections of texts that have been carefully collected for linguistic research. Although the literature in the area is extensive, there is a shortage of research dealing with the areas of Corpus Linguistics and English Language Teaching the way this research attempts to do. Two corpora have been used in this research. The main corpus, which is a collection of all the episodes of the sitcom Friends, is made up of 883,453 words; the other corpus was a reference corpus containing 4.,35,731 words from the oral component of the British National Corpus (BNC). The research questions investigated in this study aimed at the identification, in the corpora, of the most frequent lexicogrammatical patterns of the words and expressions focused by the activity in the coursebook. The analysis made it possible to select lexicogrammatical patterns for inclusion in activities that were designed to complement activities in the coursebook. These were detailed in the third chapter of the disseertation. The study presented here will hopefully make an original contribution to the existing body of corpus-based research, more specifically in the area of Corpus Linguistics and English Language Teaching, by detailing an attempt at bringing together DDL and Sociointeractionism in practical activities for the EFL classroom